2015
DOI: 10.1093/ehjci/jev071
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular echocardiographic indices predict poor outcomes in infants with persistent pulmonary hypertension of the newborn

Abstract: TAPSE, GLPS, and right-to-left PDA shunting were associated with progression to death/ECMO. RV free wall strain was not associated with the outcome, suggesting that diminished global strain better reflects clinical outcomes in this group. These thresholds may assist in the decision-making to transfer high-risk infants to ECMO centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 34 publications
(44 reference statements)
1
32
0
2
Order By: Relevance
“…These findings may reflect the response of the right ventricular myocardium to increased afterload in cases of elevated pulmonary artery pressure. 33 Our results are in agreement with the study of McCrary et al who have shown the ratio of systole over diastole duration to be higher in chronic lung disease patients with pulmonary hypertension than those without. 15 The fact that echo parameters of right ventricular performance improved quickly post-opertively in our pulmonary hypertension infants may indicate the contribution of a significant atrial shunt to elevated pulmonary artery pressure and impaired right ventricular contractility.…”
Section: Early Atrial Septal Defect Repair and Right Ventricular Perfsupporting
confidence: 94%
“…These findings may reflect the response of the right ventricular myocardium to increased afterload in cases of elevated pulmonary artery pressure. 33 Our results are in agreement with the study of McCrary et al who have shown the ratio of systole over diastole duration to be higher in chronic lung disease patients with pulmonary hypertension than those without. 15 The fact that echo parameters of right ventricular performance improved quickly post-opertively in our pulmonary hypertension infants may indicate the contribution of a significant atrial shunt to elevated pulmonary artery pressure and impaired right ventricular contractility.…”
Section: Early Atrial Septal Defect Repair and Right Ventricular Perfsupporting
confidence: 94%
“…There is limited data specific to the impact of PVR on preterm myocardial function, though a similar decline in RV performance as in term neonates is reported (25). An understanding of the impact of PVR on the myocardium is important because it may significantly modify disease pathophysiology and in term neonates may be a predictor of poor outcome (26). Fetal myocardial performance remains stable over the latter half of pregnancy (27,28), and animal data suggest that changes in loading conditions produce similar changes in contractility across gestations.…”
Section: Implications Of High Pvr On Myocardial Functionmentioning
confidence: 99%
“…These methods include: RV systolic tissue Doppler velocity (RV s′), tissue Doppler-derived basal longitudinal strain (RV BLS); tricuspid annular plane systolic excursion (TAPSE) and fractional area change (FAC). Recent evidence suggests that those parameters can determine disease severity and predict adverse outcomes in term infants with pulmonary hypertension 9. However, their applicability in the clinical setting, the influence of various physiological states and the interaction between left ventricle (LV) and RV function in preterm infants has not been adequately studied.…”
Section: Introductionmentioning
confidence: 99%